UJI EFEKTIVITAS ANTIJAMUR EKSTRAK KULIT NENAS TERHADAP JAMUR TULAR BENIH DAN PERTUMBUHAN BIBIT CABAI MERAH (Capsicum annum L.) - Rizky Qurnia Zary; Saripah Ulpah; T. Edy Sabli (Ekoagrotrop, 2023)
The research of "the effectiveness of test of antifungal pineapple peel extract against seed-borne fungus and the growth of red chili (Capsicum annum L.) seedlings". The research aimed to determine the effect of pineapple peel extract as antifungal in controlling red chili seed- borne fungus and its effect on germination and growth of red chili seeds. The recent research was carried out using a completely randomized design non factorial consisting of 5 treatments and 5 replications. The treatment factor is concentration of pineapple peel extract consisting of without pineapple peel extract, pineapple peel extract of 10%, 20%, 30%, and 40% respectivelly. The results showed that the appropriation of several concentrations of pineapple peel extract was less effective in controlling red chili seed-borne fungi in vitro, which can be seen in the results of the observed parameters for the incidence of each pathogenic fungus in seeds and the diameter of the seed colonies. The appropriation of several concentrations of pineapple peel extract has an effect on the germination of red chili seeds in vitro, which can be seen from the results of the observation parameters that sprouts appear, but have not affected the parameters of the observation of seed germination. The appropriation of several concentrations of pineapple peel extract affected the growth of red chili seedlings in soil media, which can be seen from the results of the observation parameters of the percentage of germinated seeds, and the number of live seeds and seedlings that grew normally, but had no effect on the parameters of observation of seedling height, number of leaves seeds, plant wet weight and plant dry weight).